The Efficiency of Indonesian Islamic Rural Banks: A Stochastic Frontier Analysis - Dian Agustina; Mahfud Sholihin; Annisa Fithria (Universitas Muhammadiyah Yogyakarta, 2019)
Banking plays an important role in economy acting as an intermediation institution and funding sources for business. When a bank is inefficient in the use of cost, there will be improperly used input, hindering the bank to realize its roles, functions, and objectives. Therefore, analysis of bank efficiency is strongly required. This study aims to measure and analyze the technical efficiency of Indonesian Islamic rural banks by using balanced panel data of Indonesian Islamic rural banksfromquartile I 2011 to quartile IV 2016. The sample includes 58 Islamic rural banks with total 1,392 observations. By using stochastic frontier analysis,the result shows that the average technical efficiency of IndonesianIslamic rural banksreached 86 percent and there are still 14 percent that can be optimized. Overall, the average efficiency of Indonesian Islamic rural banksincreases over the research period. In addition, this study also finds that big banks are more efficient than small banks.